Analisis y diseño de arquitectura de procesos para congresos tecnológicos - García Cerrillo, Víctor Andrés (2014)
The purpose of this project it’s to define de process that are involved in the develop of the of the “International Congress of Software Engineering, Information Systems and Information Technologies”. This congress executed by the UPC it’s an event that allow the integration of the students of the engineering career and bring them new knowledge and experience about the new technologies available on the market. This Congress it’s conformed for many events and contests that feed the knowledge of the audience. The “International Congress of Software Engineering, Information Systems and Information Technologies” will present to the audience different scientific and academic events that allow them to exchange and publish new knowledge. The events of the congress will be Magister conferences, Call for Papers, IBM Technology Day, Oracle Technology Day and Microsoft Technology Day. Nowadays there are no defined processes for the management of these events. For this reason this project is proposed to identify and document the key processes that joint the flow of activities under de development of the Congress. For the Process Architecture, the deliverables that belong to the Enterprise Business Model will be developed. Based on the analysis of a Benchmarking about the software applications for the management of events, the processes that will be developed are: Event Organization, Marketing and Logistics. For this project the Framework Zachman was chosen because it brings the different points of view required for the develop of information systems and the EUP methodology. At the end the project portfolio will be presented. In the future, the project should improve and complete the development of other Information Systems Architectures and development of support processes.